Perceived Risk Factors of Anaemia in Under-five Children among Childbearing Mothers in Owerri North Local Government Area, Imo State, Nigeria - Okeke, Kalu Mgbo; Eze-Ufodiama, Stella Chiamaka; Ejimonu, Ngozi Constance; Onuzulike, Nonye M.; Amanze-Njoku, Confidence N (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2024)
Anaemia in under-five children remains a significant health issue especially in the developing countries with Nigeria inclusive. This study investigated perceived risk factors of anaemia in under-five children among childbearing mothers (CBMs) in Owerri North Local Government Area, Imo State. Three research questions and two null hypotheses guided the study. The study adopted descriptive cross-sectional survey research design. The population for the study consisted of 40,000 CMBs in living in Owerri North Local Government Area, Imo State. The sample size was 400 CMBs drawn using multi-stage sampling procedures. A self “Perceived Risk Factors of Anaemia in Under-five Children Questionnaire (PRFAUFCQ)” was used for data collection. Descriptive statistics of mean, standard derivation and ANOVA test were used to answer the research questions and hypotheses respectively. Results indicated that CMBs in agreed on the perceived risk factors of anaemia in under-five children since mean 3.63. CMBs irrespective of their age agreed on the perceived risk factors of anaemia in under-five children: mother’s age of 3.17, 15 -24 years had x mean response of 3.17, those 25 -34 years (x = 3.32), mother aged 35 – 44years (x = 3.43) and those aged 45years and above had (x = 3.32). Also, CBMs irrespective of their level of education agreed on perceived risk factors of anaemia in under-five children: CBMs with primary education had (x = 3.59), those with secondary education (x =3.63), and mothers with tertiary education (x = 3.76). There was a significant difference in the perceived risk factors of anaemia in under-five children among mothers in Owerri North LGA based on age. Furthermore, the result showed that there was no significant difference in the perceived risk factors of anaemia in under-five children among mothers in Owerri North LGA based on level of education. The non-significant different on the perceived risk factors of anameia in under-five probably because anaemia is one of the problem children under five years in the Local Government Area encounter most. The authors recommended among others that health care workers should educate mothers especially lactating mothers and those with children under-five years of age about good dietary practices and the benefit of exclusive breastfeeding.